INVESTIGATION OF SAFETY OF BOTTLED DRINKING WATER WITH USE OF ALIVE TEST - OBJECT – PLANARIA - LYUDMILA G. ELISEEVA; IRINA A. MAKHOTINA; PETR P. GOROZHANIN; OLGA V. YURINA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The samples of drinking water in bottles were compared by organoleptic, chemical composition and safety. To determine safety the method of biotesting with Planaria (Dugesia tigrina) was used. The degree of planarian regeneration in different water samples was measured. The data obtained showed that this test object may be successfully used for assessment of safety of bottled drinking water with sufficient correlation with organoleptic properties and toxic elements content. The properties of water were shown to depend on the source and producer.